Brief History of Cardiac Arrhythmias in Facts and Photos - Sales Pereira Gondim, Davi; Quidute Arrais Rocha, Maria Eduarda; Pinto Cavalcante Miná, Camila; Quidute Arrais Rocha, Eduardo Augusto; Pereira Gondim, Francisca Tatiana; Prata Costa, Ieda; Gondim, Francisca Tatiana Pereira; Arrais Rocha, Eduardo (JOURNAL OF CARDIAC ARRHYTHMIAS, 2022)
.